Treatment with Vitamin D3 in Vitamin D Deficient Adolescents: A Pilot Study - Mohan Kumaratne MD, FAAP; Franck Vigneron PhD; Jasmine Cisneros BS, RN (SAGE Publishing, 2020)
Multiple epidemiological studies have shown that vitamin D deficiency is highly prevalent amongst adolescents in the USA. However, recommendations regarding the treatment of vitamin D deficiency in healthy adolescents are not well defined. We carried out a prospective pilot study, to determine whether treatment with 2000 international units of vitamin D3 daily for 3 months, would normalize the vitamin D levels in vitamin D deficient adolescents. Following treatment there was a 56.02% increase in the vitamin D levels from the mean baseline values and 80.39% of the subjects normalized their vitamin D levels. There were no adverse effects associated with this intervention. This study offers complementary guidelines to the existing recommendations from the American Academy of Pediatrics on the optimal dose and duration of vitamin D3 therapy in vitamin D deficient, but otherwise healthy adolescents. Further prospective, large scale, case control studies are indicated to validate our results.